2022
DOI: 10.1007/s41105-021-00353-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Syndrome (SAS) Clinical Practice Guidelines 2020

Abstract: The prevalence of sleep-disordered breathing (SDB) is reportedly very high. Among SDBs, the incidence of obstructive sleep apnea (OSA) is higher than previously believed, with patients having moderate-to-severe OSA accounting for approximately 20% of adult males and 10% of postmenopausal women not only in Western countries but also in Eastern countries, including Japan. Since 1998, when health insurance coverage became available, the number of patients using continuous positive airway pressure (CPAP) therapy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 222 publications
0
16
0
Order By: Relevance
“…Patients who were visiting the clinics affiliated with the Minato Mirai group for sleep disorders and/or diabetes mellitus between January 1, 2015 and August 31, 2018 were included in this study. Patients aged ≥20 years, who had been diagnosed with insomnia, SRBD (based on the International Classification Sleep Disorders, Third Edition diagnostic classifications), and diabetes mellitus (based on the diabetes guidelines), were included in this study [4,18]. Moreover, all included patients have had consultations in the hospital for >3 years after having been introduced to CPAP therapy.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who were visiting the clinics affiliated with the Minato Mirai group for sleep disorders and/or diabetes mellitus between January 1, 2015 and August 31, 2018 were included in this study. Patients aged ≥20 years, who had been diagnosed with insomnia, SRBD (based on the International Classification Sleep Disorders, Third Edition diagnostic classifications), and diabetes mellitus (based on the diabetes guidelines), were included in this study [4,18]. Moreover, all included patients have had consultations in the hospital for >3 years after having been introduced to CPAP therapy.…”
Section: Patientsmentioning
confidence: 99%
“…paucity of studies with regard to obstructive sleep apnea syndrome (OSAS). The 2020 guidelines on sleep apnea syndrome define OSAS as an apnea hypopnea index (AHI) ≥15, affecting approximately 10% of women and 10-20% of men in Japan [4]. A previous study reported that 80.5% of patients with diabetes mellitus had OSAS [5].…”
mentioning
confidence: 99%
“…To argue the limitations for using pulse oximetry with actigraphy, we presented validation data using a hospital-based cohort, which used polysomnography (PSG) for assessing OSA. For the coherency of terminology between these two cohorts, we described SDB in the population-based cohort as OSA because most SDB is usually due to OSA, especially in the general population (Akashiba et al, 2022).…”
Section: Study Participantsmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a chronic respiratory disease with high incidence. The prevalence of OSA has reached 20% in men and 10% in women both in Western countries and Eastern countries [1]. The pathophysiological characteristics of OSA include chronic intermittent hypoxia (CIH) induced by periodic upper airway collapse or obstruction [1].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of OSA has reached 20% in men and 10% in women both in Western countries and Eastern countries [1]. The pathophysiological characteristics of OSA include chronic intermittent hypoxia (CIH) induced by periodic upper airway collapse or obstruction [1]. Target organ injury in OSA patients has received widespread attention.…”
Section: Introductionmentioning
confidence: 99%